Avaliação da resistência flexural de resinas acrílicas polimerizadas por micro-ondas: influência do tempo de prensagem e armazenagem pós-polimerização - Dessete, Lilian Perin [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Fractures of acrylic resins for denture bases are common problems in daily dental surgeon. These fractures are initiated with the formation of cracks and propagate through areas of high concentrations of stress. The masticatory forces focus on artificial teeth reflecting different magnitudes in the areas of the bases, which in turn result in the most affected areas of strength. The flexural strength of the polymerized material must necessarily be within values compatible with the standards established in the rules so that if the device ensures longevity. Based on these considerations, the purpose of this study was to assess the importance of pressing time and storage of post-curing on the flexural strength of acrylic resins polymerized by microwave energy Cryl Wave ® Wave ® and Vipi. 60 bodies were made of the test piece for each acrylic resin studied, standardized according to Spec # 12 of the American Dental Association (65 x 10 x 2.5 mm). The finish was done in lathe and polished with sandpaper following the sequence: 200, 500, 600, 800 end 1200 . The body-of-evidence were divided into 12 groups (n = 10) distinguished: Group I - Vipi Wave - Pressing conventional Group II - Vipi Wave - Pressing conventional storage + distilled water 24 hours; Group III - Vipi Wave - Pressing conventional distilled water storage + 30 days; Group IV - Vipi Wave - Pressing 24 hours; Group V - Vipi Wave - Pressing 24 hours + 24 hours storage distilled water; Group VI - Vipi Wave - Pressing storage 30 days 24 hours + distilled water; Group VII - Wave Cryl - Pressing conventional, Group VIII - Wave Cryl - Pressing conventional storage + distilled water 24 hours; Group IX - Wave Cryl - Pressing conventional storage + distilled water 30 days; Group X - Wave Cryl - Pressing 24 hours; Group XI - Wave Cryl - Pressing 24 hours + 24 hours storage distilled...

As fraturas das resinas acrílicas de bases de próteses totais são problemas comuns no cotidiano do cirurgião-dentista. Estas fraturas se iniciam com a formação de trincas e se propagam por áreas de altas concentrações de estresses. As forças mastigatórias incidem sobre os dentes artificiais refletindo em magnitudes distintas nas áreas das bases, que resultam por sua vez em áreas de maior incidência de forças. A resistência flexural do material polimerizado deve necessariamente estar dentro de valores compatíveis com os padrões estabelecidos nas normas a fim de que se garanta longevidade ao aparelho. Com base nessas considerações, o propósito deste estudo foi verificar a importância do tempo de prensagem e da armazenagem pós-polimerização sobre a resistência flexural de resinas acrílicas polimerizadas por energia de micro-ondas Onda Cryl® e Vipi Wave®. Foram confeccionados 60 corpos - de - prova para cada resina acrílica estudada, padronizados conforme a Especificação nº 12 da American Dental Association (65 x 10 x 2,5 mm). O acabamento foi feito em torno mecânico e o polimento com lixas seguindo a seqüência: 200, 500, 600, 800 e 1200. Os corpos - de - prova foram divididos em 12 grupos (n=10) distintos: Grupo I - Vipi Wave - Prensagem convencional; Grupo II - Vipi Wave - Prensagem convencional + armazenagem 24 horas água destilada; Grupo III - Vipi Wave - Prensagem convencional + armazenagem água destilada 30 dias; Grupo IV - Vipi Wave - Prensagem 24 horas; Grupo V - Vipi Wave - Prensagem 24 horas + armazenagem 24 horas água destilada; Grupo VI - Vipi Wave - Prensagem 24 horas + armazenagem 30 dias água destilada; Grupo VII - Onda Cryl - Prensagem convencional; Grupo VIII - Onda Cryl - Prensagem convencional + armazenagem 24 horas água destilada; Grupo IX - Onda Cryl - Prensagem convencional + armazenagem água destilada 30 dias; Grupo X - Onda Cryl...
Keywords: Prótese total; Polimetil metacrilato; Polimerização; Denture, Complete